A escritura dissensual em Becos da Memória: escrevivência, memória e luta (Revista Internacional de Folkcomunicação, 2023)
This work aims to present the act of writing, present in the work Becos da Memória, by Conceição Evaristo (2017), as a form of resistance to a subalternizing social order within the context in which there is a scarcity of literacy. In this way, we intend to present arguments that bring together the theories of Spinoza, Lotman, Rancière and Derrida - among other important authors in the field of Communication - with excerpts from Becos da Memória, in order to illustrate propositions for a new way of thinking about modes of dissensual politics, considering that they transpose socially established contexts.